Organizational Culture according to the Competing Value Framework : The case of Mohammed Seddik Benyahia University – ALGERIA - KAOUACHE, Raouf; Redha, BOUGHERZA; Djamel Eddine, KAOUACHE; Ibrahim, BOULFELFEL (Al-Adab Journal, 2023)
The current study aims to identify the existing organizational culture at Mohammad Seddik Benyahia, Jijel, University, Algeria, using the Competing Value Framework of “Camerron” and “Quinn” and to investigate differences in the level of the most spread culture according to the respondent’s perspective. The study employs the descriptive method and data were collected from 430 employees and faculty using a questionnaire. Data were analyzed using Mean, t-test and ANOVA one-way tests to measure differences in the participants’ view. The study revealed the existing of all types of culture presented by “Cammeron” and “Quinn” (hierarchy, tribe, Market, innovative). In addition, results show the spread of hierarchy culture) M 32.5(, tribe culture) M 28.1(, Market culture) M 23.2(, and creative culture) M 16.1 (respectively. furthermore, a significant difference in the hierarchy culture degree due to gender, type of job, age, level of education, seniority, salary, and number of promotions has been registered. Finally, the study conclude that the development of Mohammed Seddik Benyahia University performance requires consolidation of information flux, simplify procedures and raise the level of coordination at work.